Possible therapeutic potential of a recombinant group 2 grass pollen allergen‐specific antibody fragment. Issue 2 (20th November 2013) - Gadermaier, E.; Flicker, S.; Blatt, K.; Valent, P.; Valenta, R.
Abstract The induction of blocking IgG antibodies that compete with IgE for allergen binding is one important mechanism of allergen‐specific immunotherapy. The application of blocking antibodies may be an alternative treatment strategy. A synthetic gene coding for a single‐chain fragment (ScFv) specific for the major timothy grass pollen allergen Phl p 2 was inserted into plasmid pCANTAB 5 E, and the recombinant ScFv was expressed in Escherichia coli and purified by affinity chromatography. The ScFv was tested for allergen binding by ELISA, and its association and dissociation were measured by surface plasmon resonance (Biacore) technology. The ability of the ScFv to inhibit allergic patients' IgE binding to Phl p 2 and Phl p 2‐induced basophil degranulation was studied by ELISA competition and basophil activation (CD203c) assays. We report the expression, purification, biochemical and immunological characterization of a monomeric single‐chain fragment (ScFv) of human origin specific for the major timothy grass pollen allergen, Phl p 2. The Phl p 2‐ScFv showed high affinity binding to the allergen and blocked the binding of allergic patients' polyclonal IgE to Phl p 2 up to 98%. Furthermore, it inhibited allergen‐induced basophil activation. The Phl p 2‐ScFv inhibited allergic patients' IgE binding to Phl p 2 as well as Phl p 2‐induced basophil activation and might be useful for passive immunotherapy of grass pollen allergy.